2016
DOI: 10.1007/s00221-016-4818-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-regeneration therapy using human Muse cells is highly effective in a mouse intracerebral hemorrhage model

Abstract: A novel type of non-tumorigenic pluripotent stem cell, the Muse cell (multi-lineage, differentiating stress enduring cell), resides in the connective tissue and in cultured mesenchymal stem cells (MSCs) and is reported to differentiate into multiple cell types according to the microenvironment to repair tissue damage. We examined the efficiency of Muse cells in a mouse intracerebral hemorrhage (ICH) model. Seventy μl of cardiac blood was stereotactically injected into the left putamen of immunodeficient mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…A latest study reported that Muse cells (multi‐lineage, differentiating stress‐enduring cells), novel nontumorigenic pluripotent stem cells, dwell in the connective tissue and in cultured MSCs and are reported to differentiate into multiple cell types to repair the injured tissue after ICH based on the microenvironment, which may be a tactic of WM repair …”
Section: Repair or Recovery Mechanism And Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A latest study reported that Muse cells (multi‐lineage, differentiating stress‐enduring cells), novel nontumorigenic pluripotent stem cells, dwell in the connective tissue and in cultured MSCs and are reported to differentiate into multiple cell types to repair the injured tissue after ICH based on the microenvironment, which may be a tactic of WM repair …”
Section: Repair or Recovery Mechanism And Strategymentioning
confidence: 99%
“…112 reported to differentiate into multiple cell types to repair the injured tissue after ICH based on the microenvironment, which may be a tactic of WM repair. 115 In summary, stem cell transplantation for WMI can promote axonal repair and myelin regeneration, limit the expansion of neuroinflammation, and promote functional recovery with scar formation.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results with implanted muse in mouse model indicated functional recovery models as well as positive test for NeuN and MMP-2. The muse cells were found to be firmly implanted in the mouse brain and differentiated well into neural cells to help functional recovery [118]. Another promising field that has gained attention in recent times is the implantation of induced neurons which are from the cellular reprogramming of fibroblast cells into induced pluripotent stem cells [119].…”
Section: Preclinical Studies Of Ich: Models and Drugsmentioning
confidence: 99%
“…The study reports that simvastatin led to the attenuation of brain edema and reduced cellular Intracerebral hemorrhage animal model. Intracerebral hemorrhage was established using the stereotaxic intrastriatal injection of collagenase type IV as described previously with certain modifications (15). Briefly, a total of 60 CD-1 mice (6-8 weeks old; 300-350 g body weight)…”
Section: Introductionmentioning
confidence: 99%